3D Printing Artificial Blood Vessel Constructs Using PCL/Chitosan/Hydrogel Biocomposites - YILMAZ, BETÜL; OKTAR, FAİK NÜZHET; UZUN, MUHAMMET; GÜNDÜZ, OĞUZHAN (WILEY-V C H VERLAG GMBH, 2019)
The present paper aims to overcome the problems related to previous use of autologous grafts using available synthetic grafts. To examine the optimum of the ideal vessel-like constructs parameters are produced at 230 degrees C. At this production temperature, the elastic modulus values of the constructs ranges from 56 MPa to 174 MPa. The maximum cell proliferation is obtained from PCL/7wt.%CS/5wt.%H that is tested by mitochondrial dehydrogenase activity. The structures are visualized with all constructs after cell fixation by making use of the HUVEC cell line.
Keywords: artificial; blood; vessel; biomaterials; huvecs; hydrogels; 3d printing